Penanggulangan dan Pencegahan Narkotika - Saputra, Riki (Jurnal El-Thawalib, 2022)
The problem in this research is the Prevention and Countermeasures Against Abuse and Illicit Trafficking of Narcotics, Psychotropics and other Addictive Substances. Kenagarian Ranah Sungai Magelang is one of the Kenagarians in Gunung Tuleh District, West Pasaman Regency which has the highest level of abuse and circulation cases. The purpose of this study was to find out how the Effectiveness of the Regional Regulation of West Pasaman Regency No. 2 of 2017 Article 12 concerning the prevention and control of illicit trafficking of narcotics or other addictive substances in West Pasaman District, Gunung Tuleh Kenagarian District, Magelang River Region and to find out how Siyasah's Fiqh reviews the effectiveness of this local regulation. The role of the community in the Magelang River Realm in accordance with Article 12 Number 2 of 2017 Regional Regulation of West Pasaman Regency is to participate in carrying out campaigns and disseminating information regarding the dangers of abuse and illicit trafficking of Narcotics, Psychotropics, and other Addictive Substances. The community in the Magelang River Realm Kenagarian is actively involved in campaigning and disseminating information about the dangers of abuse and illicit trafficking of Narcotics, Psychotropics, and other Addictive Substances, in the form of counseling. This counseling is in collaboration with the Head of Drug Research at the West Pasaman Police. However, in Kenagarian Ranah Sungai Magelang, prevention from the community is only a form of counseling without any activities aimed at avoiding the dangers of Narcotics such as community organizations, such as community empowerment. There is no forum for the community to actively participate in this drug prevention action.